Occlusion Images Generation from Occlusion-Free Images for Criminals Identification based on Artificial Intelligence Using Image - LEE, Yonggeol; Mook KANG, Jang (International Journal of Engineering and Technology, 2018)
In this paper, we propose the method to generate occlusion images which include sunglass and scarf from occlusion-free images for criminals identification. First, we construct an auxiliary set that has occlusion-free face image and its occluded face images from AR database. Secondly, pixel weights are determined by the statistical analysis of the degree depending on whether occlusion-free or occlusion. As the weight is closer to 1, the pixel value of original image is maintained as much as possible. Therefore, pixel values of occlusion-free region are preserved when the weights are closed to 1. Third, pixel values of the occlusion region of original image are replaced to pixel values which are the mean of occlusion images by multiplying the composited weights. As a result of generate face images with various occlusions using the proposed method, the images were able to preserve the person-specific characteristic, and criminals identification has become easier.Â Â